The effect of cyclophosphamide on cytotoxic T-lymphocyte responses: inhibition of helper T-cell induction in vitro. - Varkila, K (1983)
The effects of cyclophosphamide (Cy) on the different cell populations participating in the cytotoxic T lymphocyte (CTL) response against haptenated (trinitrophenyl, TNP) syngeneic cells were studied. Pretreatment of responder cell donor mice with 150 mg/kg Cy decreased the cytotoxicity against TNP-modified syngeneic target cells almost to the background level. When TH cells were added to the culture the cytotoxicity increased significantly. Helper T cells were generated in vivo by priming the mice with TNP-modified syngeneic spleen cells or sensitizing the mice with a reactive hapten (TNCB). However, if the TH cell donor mice were treated with Cy before in vivo priming, the cytotoxicity reached the normal level, which indicated that TH precursors were not destroyed by Cy treatment and TH induction was even more effective after Cy. These data indicate that the decrease of the response by this Cy dose is not due to the sensitivity of CTL or TH precursors. Mice could be primed with male-specific (HY) antigen in spite of Cy pretreatment. However, Cy pretreatment caused a latent period of 2 weeks when effective CTL could not be generated in vitro, but after that the capacity for CTL generation was restored. These experiments confirm that pretreatment of responder cell donor mice with Cy does not destroy CTL or TH precursors, but rather affects their in vitro restimulation probably by destroying a short lived 'inducer' cell that is needed.